Geographic Information System of Building Auction Mapping of Bank Rakyat Indonesia Inc. Bontang Branch Office - Milatus Sholihah Mukarromah; Syafei Karim; Nia Kurniadin (Politeknik Pertanian Negeri Samarinda, 2022)
Bank Rakyat Indonesia Inc. is one of the largest state-owned banks (BUMN) in Indonesia which has a mission to serve micro, small and medium enterprises to improve the community's economy. To develop the business world so that economic growth can be maintained, a large amount of funds is needed to meet the needs in the form of credit facilities. At the time of credit, if the debtor is unable to pay off the debts to the bank, the bank as the creditor will conduct an auction process for the Debtor Guarantee. From this research, a webGIS is presented with the data used is data taken by collecting building data at auction through interviews, collecting data coordinates and distributing questionnaires, from 35 respondents a score of 70.21 was obtained where the Adjective Rating was in a good position with acceptable level of acceptance. The purpose of this study is to determine the location of the auction house building and make it easier for users to know the place in detail.